Green from the ground up : a builder's guide : sustainable, healthy, and energy-efficient home construction - Johnston, David, 1950- (Taunton Press, 2008)
This thorough, informative, and up-to-date reference on environmentally conscious, energy-efficient home construction gives builders and architects the tools to respond to growing requests from homeowners for green houses.